Hypermetabolism of glutathione, glutamate and ornithine via redox imbalance in methylglyoxal-induced peritoneal injury rats. (8th October 2019) - Hirahara, Ichiro; Kusano, Eiji; Jin, Denan; Takai, Shinji
Abstract: Peritoneal dialysis (PD) is a blood purification treatment for patients with reduced renal function. However, the peritoneum is exposed to oxidative stress during PD and long-term PD results in peritoneal damage, leading to the termination of PD. Methylglyoxal (MGO) contained in commercial PD fluids is a source of strong oxidative stress. The aim of this study was to clarify the mechanism of MGO-induced peritoneal injury using metabolome analysis in rats. We prepared peritoneal fibrosis rats by intraperitoneal administration of PD fluids containing MGO for 21 days. As a result, MGO-induced excessive proliferation of mesenchymal cells with an accumulation of advanced glycation end-products (AGEs) at the surface of the thickened peritoneum in rats. The effluent levels of methionine sulfoxide, an oxidative stress marker and glutathione peroxidase activity were increased in the MGO-treated rats. The levels of glutathione, glutamate, aspartate, ornithine and AGEs were also increased in these rats. MGO upregulated the gene expression of transporters and enzymes related to the metabolism of glutathione, glutamate and ornithine in the peritoneum. These results suggest that MGO may induce peritoneal injury with mesenchymal cell proliferation via increased redox metabolism, directly or through the formation of AGEs during PD.